Environmental Crimes and Bentonite Mining and Processing Companies in Slovak Republic - Kajanová Jana; Nováček Peter (TalTech Journal of European Studies, 2022)
At the time when great emphasis is being placed on environmental protection as well as on the introduction of environmental safeguards, we are faced with an undesirable phenomenon—environmental crime. Environmental crime represents one of the fastest growing security issues. It is a criminal activity, and like other crimes, it has serious consequences that are costly to eliminate. This article uses systematic analysis and, through scientific methods, points out the growth of environmental crime in Slovakia. At the same time, it introduces possible prevention tools. Our aim is to specify the term ‘environmental crime’, present the legal aspects of environmental crimes by focusing on Slovak legal regulation, extend the topic to bentonite mining and processing companies, map environmental crime in the EU Member States, and clarify the nature of environmental crime as well as the legal basis for the protection of the environment in Slovakia. The findings and conclusions have the potential to introduce a new approach to mapping the topic of environmental crimes, provide recommendations for the prevention of this type of crime, and open a discussion on the actual global problem. It is evident that the effective fight with environmental crime requires a complex and multidisciplinary approach at all levels. This includes, in particular, the use of relevant national policies and instruments, as well as those of the European Union and other international organizations.